2023
DOI: 10.1007/s12282-022-01430-5
|View full text |Cite
|
Sign up to set email alerts
|

Oncoplastic versus conventional breast-conserving surgery in breast cancer: a pooled analysis of 6941 female patients

Abstract: Background Breast cancer is the most prevalent cancer in women. In the past few years, surgical interventions for breast cancer have experienced massive changes from radical excision to conserving approaches. In this study, we aim to compare the two breast surgery interventions, including conventional breast-conserving surgery (CBCS) versus oncoplastic breast-conserving surgery (OPBCS). Methods We searched on PubMed, Web of Science (WOS), Scopus, Embase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Currently, breast conservation in retroareolar tumours is made possible by techniques derived from plastic surgery involving removal of the PAM [4]. Oncoplastic breast surgery is a new trend in conventional breast conserving surgery that merges the concepts of oncology and plastic surgery to achieve satisfactory results both oncologically and aesthetically [10]. It allows the removal of significantly larger tumours because it has become an alternative to mastectomy for tumours larger than 4 cm and for locoregional tumours [5] [9] [10] [15] [16] [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, breast conservation in retroareolar tumours is made possible by techniques derived from plastic surgery involving removal of the PAM [4]. Oncoplastic breast surgery is a new trend in conventional breast conserving surgery that merges the concepts of oncology and plastic surgery to achieve satisfactory results both oncologically and aesthetically [10]. It allows the removal of significantly larger tumours because it has become an alternative to mastectomy for tumours larger than 4 cm and for locoregional tumours [5] [9] [10] [15] [16] [17].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of bulky tumour resection by the breast surgeon and immediate breast reconstruction by the plastic surgeon has many advantages, including safer resection with wider margins and immediate aesthetic results [9]. A pooled meta-analysis of the included studies showed that conservative treatment with oncoplasty was significantly superior to standard conservative treatment in most criteria [10].…”
Section: Introductionmentioning
confidence: 99%